O Tell Me the Truth About the Transfer of Preliminary References to the General Court. Three Narratives to Be Questioned, Two Thorny Issues to Be Introduced and One Scenario to be Addressed as the Main Legacy of the Recent Reform of the CJEU Statute - Jacopo Alberti (European Papers, 2025)
(Series Information) European Papers - A Journal on Law and Integration, 2025 10 (2), 333-356 | Article | (Table of Contents) 1. Introduction. – 2. Some narratives to be questioned. – 2.1. Dealing with oxymoron: the (alleged) specialisation of the General Court. – 2.2. Reducing (or changing) the workload of the Court of Justice? – 2.3. The constitutionalisation of the Court of Justice (and the multiple meanings thereof). – 3. The main legacy of the reform: fostering the verticalisation of the EU judiciary. – 4. Two thorny issues to be discussed. – 4.1. The legislative role of the Court of Justice: time for a reconsideration? – 4.2. How to assess whether the reform reaches its targets? | (Abstract) The article discusses the main narratives surrounding the reform, namely the increasing specialisation of the General Court, the reduction of the workload of the Court of Justice and its progressive constitutionalisation, highlighting the seed of truth that can be found in them as well as the misunderstandings on which they are based. Subsequently, it proposes a further interpretation on the long-term impact of this reform, arguing that its main legacy should more precisely be identified as the verticalisation of the EU judiciary and discussing its benefits and risks. Finally, it presents a couple of thorny issues that have not thus far attracted the attention of the debates, namely the role of the Court of Justice in the legislative process regarding the amendments of its own Statute and the benchmarks for assessing whether the reform reaches its targets.